Protein degradation following treatment with hydrogen peroxide. - Fligiel, S. E. (1984)
Pretreatment of hemoglobin with 50-5000 nmol hydrogen peroxide (H2O2) increased its susceptibility to proteolysis by a number of purified enzymes, including trypsin, chymotrypsin, elastase, and plasmin, and by the neutral protease of rat peritoneal leukocytes. Pretreatment of the protein substrate with catalase-inactivated H2O2 had no effect. Separation of the proteolytic fragments by G-75 Sephadex gel filtration indicated no apparent differences in the size distribution of the fragments produced by treatment with the H2O2/proteolytic enzyme combination as compared with enzyme treatment alone. A partially purified preparation of rat glomerular basement membrane was also treated with proteolytic enzyme alone or in combination with H2O2. As with the hemoglobin, pretreatment of the glomerular basement membrane with H2O2 increased its susceptibility to subsequent proteolytic attack. In addition, treatment of a basement membrane glycoprotein, fibronectin, with H2O2 also increased its sensitivity to subsequent proteolysis. These results suggest that in addition to their other proinflammatory activities, oxygen-derived metabolites may contribute to tissue destruction by altering the susceptibility of proteins to hydrolytic enzymes.